Masters of War: Rivals' Product Innovation and New Advertising in Mature Product Markets - Fosfuri, Andrea; Giarratana, Marco S. (Management Science, 2009)
We investigate the impact of rivals' product innovation and new advertising on a firm's financial market value in mature product markets. Our test bed is the carbonated soft drink market between 1999 and 2003, a period characterized by a near duopoly between Coca-Cola and Pespi. Empirically, we focus on new product announcements as a proxy of product innovation and on filed trademarks as a measure of new advertising. We find that rival product announcements decrease a firm's financial market value, and that rival filed trademarks increase it. Finally, we find that the effect of new advertising is channeled through market size dynamics, while that of product innovation operates through market share dynamics. Results are robust across different estimation techniques (event study, Tobin's q) and model specifications.